Irrigation water and pumping energy use trends in rice (Oryza sativa L.) under varying irrigation regimes in partially reclaimed sodic soils - SINGH, ATUL KUMAR; VERMA, C. L.; SINGH, Y. P.; BHARDWAJ, A. K.; ARORA, SANJAY; SINGH, DHANJAY (Journal of Soil and Water Conservation, 2020)
Sodic soils are characterized by a relatively low electrical conductivity (EC), high exchangeable sodium (Na) on exchange sites, soil pH > 8.0, low rate of infiltration, and dispersed soil. From crop irrigation management perspective, the major challenges for sodic soils are their low infiltration characteristics, less available water for plants due to reduced water holding capacity, and low restricted water movement from sub soil to root zone because of poor hydraulic conductivity. This requires frequently replenishing the root zone with optimum volume of water to sustain plant growth. An experiment to determine the suitable irrigation depth and frequency, along with methods of application namely: Surface (farmer’s practice), Sprinkler (double nozzle impact sprinkler), and LEWA (Low Energy Water Application) was initiated. Irrigation depth of 6 cm in case of Surface method, and 4 cm in case of Sprinkler and LEWA was applied at each irrigation event. The irrigation events were scheduled at 2-DAD (days after disappearance of water), 3-DAD and 4-DAD in case of surface method, and daily, 1-day and 2-day interval (after initial ponding disappeared) by Sprinkler and LEWA. The results revealed that grain yield varied with varying irrigation regime. Amongst surface irrigated plots the highest grain yield of 4.4 t ha-1 was obtained under highest irrigation level of 2-DAD which registered decline by 10% at 3DAD and by 25% at 4 DAD. Yield variation was marginal within Sprinkler and LEWA irrigated plots where highest yield of 4.4 t ha-1 at daily and 2-day interval in case of Sprinkler and at 2-day interval in case of LEWA was observed. Sprinkling methods (Sprinkler and LEWA) scheduled at 2-day interval resulted in water saving of 20% to 30% over surface method of irrigation (2-DAD and 3-DAD); whereas, energy use by Sprinkler was higher than Surface method (3-DAD and 4-DAD) as well as LEWA method (all irrigation regimes). This lead to to savings in energy by 20% to 30% using LEWA (at 2-day interval) over surface method of irrigation (2-DAD and 3-DAD), and, by using 5% by Sprinkler (at 2-day interval) over surface method (2-DAD).